1987
DOI: 10.1083/jcb.104.5.1223
|View full text |Cite
|
Sign up to set email alerts
|

The role of lysosomal enzymes in killing of mammalian cells by the lysosomotropic detergent N-dodecylimidazole.

Abstract: Abstract. The sensitivity of cultured human and hamster fibroblast cells to killing by the lysosomotropic detergent N-dodecylimidazole (Ct2-Im) was investigated as a function of cellular levels of general lysosomal hydrolase activity, and specifically of cysteine cathepsin activity. Fibroblasts from patients with mucolipidosis II (I-cell disease) lack mannose-6-phosphate-containing proteins, and therefore possess only 10-15 % of the normal level of most lysosomal hydrolases. I-cell fibroblasts are about one-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 28 publications
1
40
1
Order By: Relevance
“…Finally, the characteristics of siramesine-induced cell death, e.g., an early lysosome damage occurring prior to cell rounding and death, dependence on cysteine cathepsin activity and cell density as well as a highly sigmoidal dose-response curve, 10 closely resemble those of other lysosomotropic detergents. 36,38 It should, however, be noted that whereas other lysosomotropic detergents have been reported to kill all lysosome-containing cells, 37 siramesine-mediated killing displays selectivity to transformed cells both in vitro and in vivo. 10,18 Our earlier data showing that siramesine induces oxidative stress and that lipophilic but not hydrophilic anti-oxidants effectively inhibit siramesine-induced cell death have suggested that lipid peroxidation may be involved in siramesine-induced lysosomal leakage and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the characteristics of siramesine-induced cell death, e.g., an early lysosome damage occurring prior to cell rounding and death, dependence on cysteine cathepsin activity and cell density as well as a highly sigmoidal dose-response curve, 10 closely resemble those of other lysosomotropic detergents. 36,38 It should, however, be noted that whereas other lysosomotropic detergents have been reported to kill all lysosome-containing cells, 37 siramesine-mediated killing displays selectivity to transformed cells both in vitro and in vivo. 10,18 Our earlier data showing that siramesine induces oxidative stress and that lipophilic but not hydrophilic anti-oxidants effectively inhibit siramesine-induced cell death have suggested that lipid peroxidation may be involved in siramesine-induced lysosomal leakage and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we speculated that MLIV fibroblasts bearing abnormal lysosomes would be more sensitive to lysosomotropic drugs than normal cells. Dodecylimidazol was previously found to be more toxic to normal cells than mucolipidosis II cells (I cell disease) (14). Other lysosomotropic drugs, which were found to inhibit lysosomal enzymatic processing (15)(16)(17), were also tested.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinically relevant urine concentrations (0 -200 M) of CQ were used to mimic the physiological conditions of the distal tubule and used as input parameters to mathematically model transport behavior of CQ. Simulation results were compared with experimental measurements of intracellular CQ mass in dose-response and time course experiments, under conditions that either enhanced the phospholipidosis effect [cotreatment with sucrose (Wilson et al, 1987;Helip-Wooley and Thoene, 2004)] or inhibited vacuolation [cotreatment with bafilomycin A1 ].…”
Section: Introductionmentioning
confidence: 99%